Sakamoto days. Vol. 5, Death row prisoners - Suzuki, Yūto (Shonen Jump manga., 2022)
Kill some time with former hit man Taro Sakamoto! "Taro Sakamoto was once a legendary hit man considered the greatest of all time. Bad guys feared him! Assassins revered him! But then one day he quit, got married, and had a baby. He's now living the quiet life as the owner of a neighborhood store, but how long can Sakamoto enjoy his days of retirement before his past catches up to him?! The situation is fraught during the casino battle between Sakamoto's staff and the Chinese triad. Can they protect Lu and get info on the bounty?! To make matters worse, the very worst assassins from overseas are gunning for Sakamoto!"--Back cover.